Field notes contributed by Hank Zaletel, fall 1981 - Zaletel, Hanket al (1981)
Field notes were contributed by Hank Zaletel and Linda Zaletel, observer. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1981. Epson - sheet feed